THE INFLUENCE OF BARGAINING RELATIONSHIPS AND THE DEVELOPMENT OF APPROACHES TO EMPLOYEE ENGAGEMENT AND CSR - Hermanto, Ahmad (Krisnadwipayana International Journal of Management Studies, 2021)
CSR is one of the drivers of employee engagement is a trend and the attention of researchers in the business world today. Experience proves that Employee engagement helps organizations to increase profits, commitment and loyalty reduces attrition, reduce absenteeism, and accidents which in turn adds up to the revenues of the firm. This study seeks to investigate whether the model of transactional, relational, and developmental approaches is an effective approach in applying the concept of CSR as a tool for employee engagement.